Heat warnings, mortality, and hospital admissions among older adults in the United States. (December 2021) - Weinberger, Kate R.; Wu, Xiao; Sun, Shengzhi; Spangler, Keith R.; Nori-Sarma, Amruta; Schwartz, Joel; Requia, Weeberb; Sabath, Benjamin M.; Braun, Danielle; Zanobetti, Antonella; Dominici, Francesca; Wellenius, Gregory A.
Highlights: Heat warnings are issued in advance of forecast periods hot weather in the United States. Evidence on the effectiveness of warnings in reducing illness and death is limited. Heat warnings were not associated with a lower risk of mortality. Heat warnings were associated with increased risk of hospitalization for heat-related causes. Abstract: Background: Heat warnings are issued in advance of forecast extreme heat events, yet little evidence is available regarding their effectiveness in reducing heat-related illness and death. We estimated the association of heat warnings and advisories (collectively, "alerts") issued by the United States National Weather Service with all-cause mortality and cause-specific hospitalizations among Medicare beneficiaries aged 65 years and older in 2, 817 counties, 2006–2016. Methods: In each county, we compared days with heat alerts to days without heat alerts, matched on daily maximum heat index and month. We used conditional Poisson regression models stratified on county, adjusting for year, day of week, federal holidays, and lagged daily maximum heat index. Results: We identified a matched non-heat alert day for 92, 029 heat alert days in 2, 817 counties, or 54.6% of all heat alert days during the study period. Contrary to expectations, heat alerts were not associated with lower risk of mortality (RR: 1.005 [95% CI: 0.997, 1.013]). However, heat alerts were associated with higher risk of hospitalization for fluid and electrolyte disorders (RR: 1.040 [95% CI: 1.015, 1.065]) and heat stroke (RR: 1.094 [95% CI: 1.038, 1.152]). Results were similar in sensitivity analyses additionally adjusting for same-day heat index, ozone, and PM2.5 . Conclusions: Our results suggest that heat alerts are not associated with lower risk of mortality but may be associated with higher rates of hospitalization for fluid and electrolyte disorders and heat stroke, potentially suggesting that heat alerts lead more individuals to seek or access care.